Biblical Techniques for the Interpretation of the Nicene Creed: the Case of Athanasius’ De synodis (Ferdinand Schöning / Brill, 2020)
The Trinitarian controversy of the 350s revolved around synodical texts, because the term ‘consubstantial’ (ὁμοούσιος), proclaimed by the synod of Nicaea (325), was rejected by many of the eastern bishops. For the first time in history, an important theological discussion was shaped not only by the interpretation of Scripture but also the understanding of a creed. Within this new institutional and theological context, Athanasius of Alexandria, in his work De synodis (359), made a serious attempt to establish criteria for interpreting synodical texts. The present article studies Athanasius’ effort to apply biblical hermeneutical criteria to the interpretation of synodical documents. In order to shed light on this innovative contribution of Athanasius, the article proceeds as follows: first, I review the historical and theological context of his activity; second, I examine each of the objections to the Nicaean creed and the solutions offered by the Bishop of Alexandria; finally, I explore the rationale of Athanasius’ interpretation of synodical documents and its significance for the formation of Christian discourse.